Burst spinal cord stimulation in a patient with a cardiac pacemaker - Fattibilità dell'impianto di SCS con stimolazione Burst in un paziente con pacemaker cardiaco - Giuliano De Carolis; Giulio Zucchelli (Publiediting, 2016)
A 74-year-old male suffering from neuropathic pain in the distal portion of the lower limbs had obtained no relief from medical treatments. Additional comorbidities included pacemaker-dependent complete (3rd degree) atrio-ventricular block and a prolactin-secreting adenoma of the pituitary gland. An electrocatheter was implanted in the epidural space, with the active leads spanning the T10-T11 vertebral levels. Intraoperative stimulation tests were performed in both tonic and burst modes while pacemaker activity was monitored in real time. SCS stimulation intensity was increased in steps up to the threshold of patient tolerability (7.5 mA tonic, 3.9 mA burst). Pacemaker sensitivity was set to the maximum (0.5 mV): during the procedure, no interference with pacemaker sensing was observed. To the authors' knowledge, this is the first case report on the feasibility of burst SCS in a pacemaker-dependent patient. The report suggests that burst stimulation is safe in such patients.